Process evaluation of the 90-90-90 targets of surge project in Addis Ababa, Ethiopia: a case study evaluation - Belete Kefyalew Eshetu; Tesfahun Zemene Tafere; Geta Asrade; Tsegaye Gebremedhin Haile (BMC, 2024)
Abstract Background Human Immunodeficiency Virus (HIV) is a major public health problem that continues to pose an enormous challenge to mankind's survival worldwide. In urban Ethiopia, the HIV prevalence among adults aged 15-49 years is 2.9%, while in Addis Ababa, it is 3.4%. To take the edge off, the Ethiopian government has been implementing the 90-90-90 strategy also known as the surge project, in urban cities. However, the implementation of the program has not been evaluated. Thus, we evaluated the process of the 90-90-90 targets of the surge project in Addis Ababa, Ethiopia. Methods We conducted a case study with concurrent mixed-methods evaluation. We used indicator-driven evaluation dimensions -availability and accommodation dimensions from the health services access and compliance and fidelity from implementation fidelity frameworks to test the program process theory with a total of 52 indicators. We interviewed a total of 419 clients and 210 healthcare providers and reviewed 417 clients' cards and 17 registries. We also conducted 30 key informant interviews and resource inventory. A binary logistic regression analysis was done to identify factors associated with clients' satisfaction. We transcribed and translated the qualitative data and analysed thematically. Finally, we judged the overall process of the surge project based on the pre-seated judgmental criteria as; needs urgent improvement, needs improvement and well implemented. Results We found that 90% of the project process was as per the program process theory measured by the availability of resources (95.8%), compliance (88.0%), fidelity (84.7%), and accommodation of services (89.3%). We found a shortage of human power, test kits, and viral load testing machines. The commitment of health care providers, provider-client interaction, and clients' satisfaction with the service at card rooms were found to be poor. Moreover, being aged 15-24, being married and government government-employed were negatively associated with clients' satisfaction with antiretroviral therapy services. Conclusion The process of the surge project needs improvement. Moreover, the achievements of the first two 90-90 targets were poor. Therefore, implementers need to take intensified action for the availability of resources and to improve the commitment of healthcare providers through refreshment training.